Virulence and Antibiotic Resistance Characteristics of Vibrio Isolates From Rustic Environmental Freshwaters - Gxalo, Oyama; Digban, Tennison O.; Igere, Bright E.; Olapade, Ola A.; Okoh, Anthony I.; Nwodo, Uchechukwu U. (Frontiers in Cellular and Infection Microbiology, 2021)
The study investigated the occurrence of antimicrobial resistance genes and virulence determinants in Vibrio species recovered from different freshwater sheds in rustic milieu. A total of 118 Vibrio isolates comprising Vibrio fluvialis (n=41), Vibrio mimicus (n=40) and V. vulnificus (n=37) was identified by amplification of ToxR, vmh and hsp60 genes. The amplification of virulence genes indicated that V. mimicus (toxR, zot, ctx, VPI, and ompU) genes were detected in 12.5%, 32.5%, 45%, 37.5% and 10% respectively. V. fluvialis genes (stn, hupO and vfh) were harboured in 48.8%, 14.6% and 19.5% isolates congruently. The other virulence genes that include vcgC and vcgE were observed in 63.1% and 29% of isolates belonging to V. vulnificus. With the exceptions of imipenem, meropenem and ciprofloxacin, most isolates exhibited more than 50% resistance to antibiotics. The antimicrobial resistance was more prevalent for polymyxin B (100%), azithromycin (100%) and least in ciprofloxacin (16.1%). Multiple antibiotic resistance index range was 0.3 and 0.8 with most isolates showing MARI of 0.8. The blaTEM, AmpC, blaGES, blaIMP, blaOXA-48 and blaKPC genes were detected in 53.3%, 42%, 29.6%, 16.6%, 15%, 11.3% and 5.6% of the isolates. Non-beta lactamases such as streptomycin resistance (aadA and strA), gentamicin resistance (aphA1) and quinolone resistance gene (qnrVC) were found in 5.2%, 44.3%, 26% and 2.8%. Chloramphenicol resistance genes (cmlA1 and catII) were found in 5.2% and 44.3% among the isolates. Our findings reveal the presence of antimicrobial resistance genes and virulent Vibrio species in aquatic environment which can have potential risk to human and animal’s health.